Reactive melt crosslinking of cellulose nanocrystals/poly(ε-caprolactone) for heat-shrinkable network. (December 2022) - Avella, Angelica; Idström, Alexander; Mincheva, Rosica; Nakayama, Koyuru; Evenäs, Lars; Raquez, Jean-Marie; Lo Re, Giada
Abstract: Focusing on the challenge of non-biodegradable plastics replacement, we propose a design for peroxide-initiated crosslinking of biodegradable poly(ε-caprolactone) (PCL) and renewable cellulose nanocrystals (CNCs) bionanocomposites. An industrially scalable water-assisted reactive melt-processing (REx) is studied to explore the hypothesis of synergy between simultaneous effects of water on improving CNC dispersion and boosting PCL branching/crosslinking. We demonstrate that the melt processing control enables the preparation of targeted thermoplastic/thermoset bionanocomposites with gel content up to ≈ 40 %, identified as the limit of their melt-processability. Structural characterization reveals that ≈ 70 wt% of the initial CNC content is irreversibly incorporated in a percolating network, enhancing the crosslinked bionanocomposites properties. The bionanocomposites' complex viscosity and elastic character increase with the gel content, thus improving PCL melt performance. Furthermore, the irreversible entrapment of CNCs in the 3D percolating network provides heat-shrinkability, indicating a potential of the reacted bionanocomposites for heat-triggered shape-memory.